2022
DOI: 10.3390/ejihpe12120124
|View full text |Cite
|
Sign up to set email alerts
|

State of Mind Assessment in Relation to Adult Attachment and Text Analysis of Adult Attachment Interviews in a Sample of Patients with Anorexia Nervosa

Abstract: Background: Attachment theory represents one of the most important references for the study of the development of an individual throughout their life cycle and provides the clinician with a profound key for the purposes of understanding the suffering that underlies severe psychopathologies such as eating disorders. As such, we conducted a cross-sectional study with a mixed-methods analysis on a sample of 32 young women with anorexia nervosa (AN); this study was embedded in the utilized theoretical framework wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 120 publications
2
3
0
Order By: Relevance
“…linguistic profiles. This study found that dismissing and secure attachment are the most prevalent classifications when compared to preoccupied attachment, which is consistent with the results obtained when comparing the overall number of occurrences related to an attachment category: secure and dismissing are greater than preoccupied attachment, and thus these results are in the same direction as a previous study conducted by Civilotti et al [13], which used the same concept of examining the content validity using the text analysis, through which they assumed that the prevalence of dismissing attachment in women with anorexia would be associated to linguistic profiles of dismissing attachment. Although the study of Civilotti et al [13] found a coexistence of preoccupied attachment and linguistic profiles of dismissing, this slight deviation in the lexical field used may be due to the specificity of this sample in terms of the effect of emotional complexity, which is an excluded possibility in the sample of the current research because it's not currently undergoing any psychological or physical treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…linguistic profiles. This study found that dismissing and secure attachment are the most prevalent classifications when compared to preoccupied attachment, which is consistent with the results obtained when comparing the overall number of occurrences related to an attachment category: secure and dismissing are greater than preoccupied attachment, and thus these results are in the same direction as a previous study conducted by Civilotti et al [13], which used the same concept of examining the content validity using the text analysis, through which they assumed that the prevalence of dismissing attachment in women with anorexia would be associated to linguistic profiles of dismissing attachment. Although the study of Civilotti et al [13] found a coexistence of preoccupied attachment and linguistic profiles of dismissing, this slight deviation in the lexical field used may be due to the specificity of this sample in terms of the effect of emotional complexity, which is an excluded possibility in the sample of the current research because it's not currently undergoing any psychological or physical treatment.…”
Section: Discussionsupporting
confidence: 91%
“…We used the lexical approach to analyze the interview transcript given the fact that classifications are at the core of empirical and theoretical research on adult attachment [3] and words have historically been considered to reveal the individuals, thoughts, feeling, and way of thinking [13]. After classifying the interviews, we examined the validity of the content, following the same method adopted by Loritio and Scrima [8],that hypothesized that participants with the same attachment style would use similar semantic systems, and those who belong to different categories of attachment would use disparate semantic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all studies of AN, cortical activity has been consistently described in the PFC, ACC, SFG, MFG, IFG and OFC, whereas a clear trend has not emerged regarding activity in the limbic areas (HYP, AMG, HIP and INS), although it appears that neuronal activity is increased in these areas [ 79 , 81 ]. This finding is consistent with other original research and meta-analytic studies [ 78 , 106 , 107 ] and also with the clinical observation that patients with AN have a cognitive profile that targets high levels of top-down control, in conjunction with emotional dysregulation that is poorly recognized and difficult to manage [ 108 ]. The lateral part of the PFC is specifically human and performs control functions in selection of tasks that drive behavior [ 109 ].…”
Section: Discussionsupporting
confidence: 91%
“…This hyperactivation could also play a role in interoceptive perception and hunger state detection (involving corticolimbic structures such as the AMG) or appetite regulation (involving the hypothalamus). These aspects are extremely impaired in AN patients, probably not only because hunger stimuli are not taken into account at the explicit level but also, especially in the most severe cases, due to a rigid mechanism of semantic top-down control that impairs adequate regulation of food intake and affects the limbic components of the brain [ 108 ]. Furthermore, it is interesting to note that top-down activations are mostly related to motivational processes that point at personal meanings and values [ 112 , 113 , 114 ], which might be reflected in the clinical manifestations of AN, such as perfectionism, low self-esteem, low self-confidence, lack of awareness of emotions and attempts to control them, especially in relation to the restricted subtype [ 13 , 115 , 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%